2018
DOI: 10.1016/j.jpainsymman.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphisms in TAOK3 Are Associated With High Opioid Requirement for Pain Management in Patients With Advanced Cancer Admitted to a Tertiary Palliative Care Unit

Abstract: In this cohort of patients with advanced cancer pain, TAOK3 SNPs were associated with opioid doses. This result supports the original findings from a GWAS in postoperative patients. The proportions of variant homozygotes (8.2% of patients) and their requirement for higher doses of opioids would appear potentially clinically important and should be validated in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Interestingly, TAOK2 was found to be recruited to the internalization vacuole containing intracellular bacteria in Listeria monocytogenes infected cells and involved in regulation of vacuolar rupture and cytoplasmic access of these bacteria [ 73 ]. Genetic variations in the TAOK3 locus rs795484 were reported to be associated with increased morphine requirement in children of European Caucasian ancestry and with increased acute postoperative pain in both European Caucasian and African American subjects [ 74 , 75 ], although the underlying mechanism is unknown and requires further determination [ 76 ]. It has been proposed that TAOK3 may act as a pharmacogene that affects the response to analgesic treatment [ 77 ].…”
Section: Tao Kinases In Other Physiological Processes and Diseasesmentioning
confidence: 99%
“…Interestingly, TAOK2 was found to be recruited to the internalization vacuole containing intracellular bacteria in Listeria monocytogenes infected cells and involved in regulation of vacuolar rupture and cytoplasmic access of these bacteria [ 73 ]. Genetic variations in the TAOK3 locus rs795484 were reported to be associated with increased morphine requirement in children of European Caucasian ancestry and with increased acute postoperative pain in both European Caucasian and African American subjects [ 74 , 75 ], although the underlying mechanism is unknown and requires further determination [ 76 ]. It has been proposed that TAOK3 may act as a pharmacogene that affects the response to analgesic treatment [ 77 ].…”
Section: Tao Kinases In Other Physiological Processes and Diseasesmentioning
confidence: 99%
“…Individual SNP associations are not necessarily responsible for phenotype; causal SNPs could be in linkage disequilibrium with those studied. Finally, we expect that rare variants and additional GWAS-identified loci, such as TAOK3 , now showing increased importance across other clinical pain and analgesia phenotypes, 63 will become essential components of larger and more precise genetic testing arrays for morphine analgesia and acute postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…In another GWAS study, TAOK3 was identified as a genetic predisposition to loneliness (Abdellaoui et al, 2019), a status that accompanies NDDs (Kwan et al, 2020;Papagavriel et al, 2020). In addition, two independent GWAS analyses showed that TAOK3 is related to high opioid requirement for patients with advanced cancer pain (Gutteridge et al, 2018) and morphine requirement for postoperative pain in a retrospective pediatric day surgery population (Cook-Sather et al, 2014), suggesting a functional role of TAOK3 in controlling pain under certain conditions. Since the impairment of sensory perception/processing is highly associated with NDDs, like autism (Robertson and Baron-Cohen, 2017), the possible function of TAOK3 in NDDs is further implied.…”
Section: Taok3mentioning
confidence: 99%